Choice and patronage: a study of retail consumers in Zimbabwe - Mlambo, Sephath; Marufu, Barbra (Scholedge, 2016)
This research focused on one specific consumer group of lecturer at Midlands State University in the city of Gweru in central Zimbabwe in order to investigate their shopping choice and patronage behaviour for a restricted range of basic commodities and foodstuffs. The research also sought to gain some insight the levels of awareness of environmental issues among an elite segment of Zimbabwean consumers. It also sought to find out how demographic characteristics [age, gender, income, marital status, and education and household size] influence patronage and shopping behaviour. A positivist perspective was adopted. Data was collected on aspects of shopping behaviour and relationships patterns and regularities were described as evidenced by the data gathered. A survey was carried out to answer ‘what’, ‘who’ ‘where’ ‘how much’ or ‘how many’ to understand the grocery shopping behaviour of the lecturers. Questionnaires were used to collect standardized data from the population in an economical way. Such data allowed for comparison and analysis using descriptive statistics. The research found out that the targeted group has exhibit a greater concern and awareness of health and the environment. The research also found out that shoppers are attracted by low competitive prices, staff attitude towards customers, ambiance, quality of products, variety and parking space.